Economic stress and well-being in urban Guyana : a microanalysis - Wilson, Leon C. (2007)
Analyzes economic stress reported by urban respondents at two time points. Isolates individual and structural characteristics of households that may account for the variation in economic stress. Provides a critical look at the actual economic conditions of real citizens.